2020
DOI: 10.3390/w12061679
|View full text |Cite
|
Sign up to set email alerts
|

Reasons of Acceptance and Barriers of House Onsite Greywater Treatment and Reuse in Palestinian Rural Areas

Abstract: In the last twenty years, house onsite wastewater management systems have been increasing in the West Bank’s rural areas. The aim of this research was to reveal, in the context of providing onsite Grey Water Treatment Plants (GWTPs) for wastewater management in the rural communities in Palestine, the local population’s perceptions, in the sense of acceptance of and barriers towards such a type of wastewater management, so as to figure out successes, failures and lessons. The data collection tool was a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
19
1
1
Order By: Relevance
“…The negative perceptions of onsite GWTPs in Palestine were due to the need to separate the house internal black and gray water (GW) conveying pipes; refusal to use the reclaimed GW in garden irrigation; non-availability of external funding; and unaffordable construction costs [24]. Problems related to cesspits are significant from the point of view of health, environment, as well as the social and economic aspects.…”
Section: Introduction 1general Informationmentioning
confidence: 99%
“…The negative perceptions of onsite GWTPs in Palestine were due to the need to separate the house internal black and gray water (GW) conveying pipes; refusal to use the reclaimed GW in garden irrigation; non-availability of external funding; and unaffordable construction costs [24]. Problems related to cesspits are significant from the point of view of health, environment, as well as the social and economic aspects.…”
Section: Introduction 1general Informationmentioning
confidence: 99%
“…Some authors reported opposite data on the effect of gray water on yields from some crops: negative effect on the growth / yield and alteration on the chlorophyll content and total crude protein of beans (IKHAJIAGBE et al 2020), presence of toxic elements which can affect a person's health (PINTO and MAHESHWARI,2015), odor emission and insect infestation (THAHER et al, 2020).…”
Section: Description Of the Graywater Reuse Program For Agricultural mentioning
confidence: 99%
“…Thus, they propose that the reuse of greywater should be oriented to 'light' greywater, since the costs of treatment and technological complexity would be lower. However, most of the research has been focused on the performance of treatment systems and their technical characteristics (i.e., [5,[16][17][18][19][20]), while economic aspects that are critical for long-term sustainability have been approached considering particular case studies in different countries of the world [21][22][23][24][25][26][27]. Furthermore, there are no experiments that have addressed the economic viability of 'light greywater' treatment systems, compared to 'dark greywater' treatment systems.…”
Section: Introductionmentioning
confidence: 99%